Detection performance and prognostic value of initial bone marrow involvement in diffuse large B-cell lymphoma - Doma, Andrej (Radiology and oncology (Ljubljana), 2024)
Detection of bone marrow involvement (BMI) in diffuse large B-cell lymphoma (DLBCL) typically relies on invasive bone marrow biopsy (BMB) that faces procedure limitations, while 18F-FDG PET/CT imaging offers a noninvasive alternative. The present study assesses the performance of 18F-FDG PET/CT in DLBCL BMI detection, its agreement with BMB, and the impact of BMI on survival outcomes. Patients and methods This retrospective study analyzes baseline 18F-FDG PET/CT and BMB findings in145 stage II–IV DLBCL patients, evaluating both performance of the two diagnostic procedures and the impact of BMI on survival. Results DLBCL BMI was detected in 38 patients (26.2%) using PET/CT and in 18 patients (12.4%) using BMB. Concordant results were seen in 79.3% of patients, with 20.7% showing discordant results. Combining PET/CT and BMB data, we identified 29.7% of patients with BMI. The sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and accuracy of PET/CT for detecting DLBCL BMI were 88.4%, 100%, 100%, 95.3%, and 96.5%, respectively, while BMB showed lower sensitivity (41.9%) and NPV (46.8%). The median overall survival (OS) was not reached in any gender subgroup, with 5-year OS rates of 82% (total), 84% (female), and 80% (male) (p = 0.461), while different International Prognostic Index (IPI) groups exhibited varied 5-year OS rates: 94% for low risk (LR), 91% for low-intermediate risk (LIR), 84% for high-intermediate risk (HIR), and 65% for high risk (HR) (p = 0.0027). Bone marrow involvement did not impact OS significantly (p = 0.979). Conclusions 18F-FDG PET/CT demonstrated superior diagnostic accuracy compared to BMB. While other studies reported poorer overall and BMI 5-year OS in DLBCL, our findings demonstrated favourable survival data.
Keywords: biopsija; biopsy; bone marrow; diffuse large B-cell lymphoma; difuzni velikocelični limfom B; kostni mozeg